Erdoğan the builder in northern Cyprus : Turkish president Recep Tayyip Erdoğan's visit to the "Turkish Republic of Northern Cyprus" cements a shift in Turkey's Cyprus policy and reinforces Ankara's isolation - Seufert, Günter (2021)
Zusammenfassung: Ahead of his trip to Turkish-occupied northern Cyprus on July 20, 2021, the Turkish President announced that he would be bringing "good news" to the Turkish Republic of Northern Cyprus (TRNC). Speculation ran rampant that Erdoğan would use the 47th anniversary of the Turkish invasion to announce that Azerbaijan, Pakistan, or Kyrgyzstan would establish diplomatic relations with the TRNC, which is currently recognized only by Turkey. But Erdoğan merely unveiled the construction of a pompous presidential palace that would befit a future, independent “Turkish Cypriot State”. The Turkish president is still reluctant to back up his words of international recognition of the TRNC with deeds. But the visit shows that Ankara is working toward the final division of the island, and Erdoğan’s actions made it clear once again that he alone calls the shots in northern Cyprus